Analisis Pengaruh Penggunaan Media Sosial Terhadap Perkembangan Bahasa Indonesia Pada Siswa SMP - Lestari Waruwu; Syukur Berkat Zai; Sesilia Putri Kurniwati Tafona'o; Agung Harapan Harefa (Departement of Mathematics Education, 2024)
This research is based on the importance of innovation in the learning process so that students can receive the material well. Technological developments in this modern era are increasingly rapid. As time goes by, the technology produced also becomes more sophisticated. In this research, researchers used qualitative research with a descriptive approach. This research can have implications for class VIII middle school students regarding the influence or impact of current use of social media. In this era of modernization, developments at the level of slang language are very rapid and even now this slang language is used as fun and enjoyable material. By using social media, you can see and pay attention to student learning outcomes. Because in the daily life of junior high school students you can see the way they learn with the help of using social media. Students can be observed from studying in class, sometimes using slang to tell stories to their friends, one of which is